Retrieval of aerosol optical depth using satellite data associated with ground-based observations over urban and rural areas Računanje optičke dubine aerosola na temelju satelitskih podataka povezanih s opažanjima na tlu u urbanim i ruralnim područjima - Le, Le Thi; Hang, Hang Thi Thuy; Cao, Cuong Xuan; Nguyen, Nghia Viet; Nguyen, Long Quoc; Le, Ha Thi Thu; Pham, Lan Thi; Le, Canh Van; Tang-Huang, Lin; Lapaine, Valentin, prevoditelj (2019)
Aerosol optical depth (AOD) can be retrieved accurately with sequential ground-based measurements of direct and diffuse solar radiance. However, spatial coverage and location frequency cause certain limitations. Hence, satellite image data are a proper tool for obtaining aerosol optical depth products with more spatial information and patterns of aerosol distribution. Currently, aerosol remote sensing may enhance our understanding of the optimal approach to AOD retrieval over urban and rural areas, and how it differs due to the characteristics of surface reflectivity. The article deals with the concepts of contrast reduction, and dark target approaches are examined using Landsat imaging and the observation of a sun photometer for integrating aerosol optical depth distribution over the city of Taipei in Taiwan. For areas with bright surfaces, such as urban areas, the above concepts were applied using the dispersion coefficient method with a sun photometer, in order to reduce errors considerably in the product. In contrast, a dark target algorithm with a relationship of surface reflectance between the blue (0.49 μm), red (0.66 μm), and infrared (2.1 μm) spectral bands is suitable for moist soils and vegetation areas. The retrieval of AOD spatial distribution is compared with MODIS AOD products and AERONET to verify the accuracy of the results. The RMSE ranged from 0.2 to 0.4, and about 50% of the data were within expected error margins (EE=± (0.05+0.15 AODsunphotometer).
Optičku je dubinu aerosola (AOD) moguće točno izračunati na temelju uzastopnih mjerenja izravnog i difuznog Sunčeva zračenja na tlu. Međutim, prostorna pokrivenost i frekvencija lokacije uzrokuju određena ograničenja. Stoga su satelitske snimke ispravan alat za dobivanje proizvoda optičke dubine aerosola s više prostornih informacija i obrazaca raspodjele aerosola. Daljinskim istraživanjima aerosola možemo bolje razumjeti najbolji pristup računanju optičke dubine aerosola u urbanim i ruralnim područjima i mogu se uočiti razlike zbog svojstava površinske reflektivnosti. Ovaj se članak bavi konceptima smanjenja kontrasta i pristupima tamnih meta koji se ispituju snimkama Landsata i opažanjima Sunčevog fotometra za povezivanje raspodjele optičke dubine aerosola iznad grada Taipeija u Tajvanu. Za područja sa svijetlim površinama kao što su gradovi navedeni se koncepti primjenjuju metodom koeficijenta disperzije zajedno sa Sunčevim fotometrom kako bi se u velikoj mjeri smanjile pogreške. Za razliku od toga, algoritam tamne mete s odnosom površinske refleksije između plavih (0,49 μm), crvenih (0,66 μm) i infracrvenih (2,1 μm) spektralnih pojaseva prikladan je za vlažno tlo i područja s vegetacijom. Računanje prostorne raspodjele optičke dubine aerosola uspoređuje se s proizvodima MODIS AOD-a i AERONET-a kako bi se provjerila točnost rezultata. RMSE je bio u rasponu od 0,2 do 0,4 i oko 50% podataka bilo je unutar granica očekivane pogreške (EE=± (0,05+0,15 AODsunphometer).
Bibliografija: 13 jed.
Summary ; Sažetak.
Tekst usporedno na engl. i hrv. jeziku.
Keywords: Aerosoli -- Optička dubina -- Daljinska istraživanja -- Satelitske snimke; Taipei -- Tajvan